Uralic typology in the light of a new comprehensive dataset - Norvik Miina; Yingqi JIng; Dunn Michael; Forkel Robert; Honkola Terhi; Klumpp Gerson; Kowalik Richard; Metslang Helle; Pajusalu Karl; Piha Minerva; Saar Eva; Saarinen Sirkka; et al. (John Benjamins Publishing Company, 2022)
This paper presents the Uralic Areal Typology Online (UraTyp 1.0), a typological dataset of 35 Uralic languages and a total of 360 features, mainly covering the levels of morphology, syntax, and phonology. The features belong to two different datasets: 195 features’ definitions originate from the Grambank (GB) database, developed for comparison of world language typology, whereas 165 features (UT) have been designed specifically to describe the typological variation within the Uralic language family. We present a series of analyses of the dataset demonstrating its scope and possibilities. The complete data set correctly identifies the main Uralic subgroups in a Principal Components Analysis, whereas GB data alone is insufficiently granular to detect this family-internal structure. Similar analyses limited to various typological subdomains also give variable results. A model-based admixture analysis identifies four distinct areas of historical interaction: Saami, Finnic, the Volga area and Ob-Ugric. Keywords: Uralic languages, typology, areal linguistics, syntax, morphology, phonology, quantitative linguistic